2005
DOI: 10.1124/jpet.105.084772
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast Prevents the Progression of Experimental Diabetic Nephropathy through Suppression of Enhanced Extracellular Matrix Gene Expression

Abstract: The present study was performed to investigate the effects of the antiallergic drug tranilast on the development of diabetic nephropathy in streptozotocin (50 mg/kg)-induced diabetic spontaneously hypertensive rats (SHR). Diabetic SHR were given standard chow or chow containing tranilast at a dose of 1400 mg/kg for 24 weeks. The effects of tranilast on urinary albumin excretion, mesangial expansion, expression of transforming growth factor-␤ (TGF-␤) and type I collagen mRNAs, number of anionic sites on the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…In addition to its anti-proliferative effects, tranilast can inhibit various inflammatory responses [33][34][35], TGF-␤ production [26], and collagen production [36], all of which would be expected to negatively impact adhesion formation [37,38]. This same reduction in TGF-␤ and type 1 collagen was demonstrated in the kidneys of rats following streptozotocin induced diabetic nephropathy as well as in the heart of mRen-2 diabetic rats [39,40]. Tranilast dependent reduction in fibrosis was also found in mice FIG.…”
Section: Discussionsupporting
confidence: 53%
“…In addition to its anti-proliferative effects, tranilast can inhibit various inflammatory responses [33][34][35], TGF-␤ production [26], and collagen production [36], all of which would be expected to negatively impact adhesion formation [37,38]. This same reduction in TGF-␤ and type 1 collagen was demonstrated in the kidneys of rats following streptozotocin induced diabetic nephropathy as well as in the heart of mRen-2 diabetic rats [39,40]. Tranilast dependent reduction in fibrosis was also found in mice FIG.…”
Section: Discussionsupporting
confidence: 53%
“…In the present diabetic nephropathy model, we were able to observe a reduction in TGF-β1 renal expression after treatment with bone marrow-derived MCs, along with a reduction in the glomerular filtration rate and glomerular tuff area to CTRL animal levels. The same observation was made in spontaneous hypertensive rats subjected to diabetes where the inhibition of TGF-β1 expression by tranilast, an antiallergic drug that inhibits the release of cytokines from macrophages and chemical mediators from mast cells [41], led to a reduction in glomerular hyperfiltration and glomerular tuff area expansion despite persistent hyperglycemia [42]. …”
Section: Discussionmentioning
confidence: 90%
“…This indicated that tranilast suppressed the accumulation of collagen in renal tissues and it may be a useful drug for diabetic nephropathy. In one survey, tranilast inhibited the diabetes-induced expansion of mesangial, decreased albuminuria by suppressing glomerular hyperfiltration, and it also suppressed the up-regulation of TGF-␤ and collagen expression in diabetic rats as well [147].…”
Section: Tranilast Against Diabetesmentioning
confidence: 99%